2014
DOI: 10.1186/s12916-014-0219-x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled clinical trial of topical insulin-like growth factor-1 therapy for sudden deafness refractory to systemic corticosteroid treatment

Abstract: BackgroundTo date, no therapeutic option has been established for sudden deafness refractory to systemic corticosteroids. This study aimed to examine the efficacy and safety of topical insulin-like growth factor-1 (IGF-1) therapy in comparison to intratympanic corticosteroid therapy.MethodsWe randomly assigned patients with sudden deafness refractory to systemic corticosteroids to receive either gelatin hydrogels impregnated with IGF-1 in the middle ear (62 patients) or four intratympanic injections with dexam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 28 publications
0
57
0
1
Order By: Relevance
“…Patient demographics and outcome data on treatment modalities extracted from the 20 RCTs [27,28,31,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51] included in the present review are reported in Table 3 and summarized in Table 4. A total of 2445 patients were treated with a NF, while the remaining 1529 patients were assigned to the placebo group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patient demographics and outcome data on treatment modalities extracted from the 20 RCTs [27,28,31,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51] included in the present review are reported in Table 3 and summarized in Table 4. A total of 2445 patients were treated with a NF, while the remaining 1529 patients were assigned to the placebo group.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining six articles [36,38,48,49,50,51] concluded the NF therapy to be effective (Table 3), which will be discussed in the next subsection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A prospective clinical study using hyaluronic acid with dexamethasone for the 514 treatment of sudden sensorineural hearing loss or Menière's disease, compared to systemic 515 steroid and vasoactive therapy, have shown significant improvement of auditory function 516 without systemic or local side effects.517 Nakagawa et al, (2014)examined the efficacy and safety of gelatin hydrogel containing IGFlocal inner ear therapy based on hydrogel formulations(Table 6). Otonomy 523 is developing OTO-104 (poloxamer 407 hydrogel containing dexamethasone)(Lambert et al, 524 2012).…”
mentioning
confidence: 99%